Transforming the teacher-student relationship: Collaborative learning in adult education - Ruth Marcus Bounous (Adult Education Research Conference, 1996)
Questions explored in this study are: Do deliberately structured collaborative relationships between teachers and adult students result in learning for both teachers and students? If yes, what learning outcomes can be expected? What are the principles of collaborative relationships that result in this learning? The research setting was a nonformal adult education program directed by the researcher at a University in New York State. In the program, university employees (the "students") are linked in collaborative relationships with under-graduate students (the "teachers") for the purpose of improving the employees’ literacy skills. The methodology is based on the assumption that knowledge is socially constructed. Data collection was triangulated, using document analysis, focus groups, and interviews. Findings were that both teachers and adult students learned through the collaborative relationships. Outcomes for adult students included increased knowledge, skills, self-confidence, and pride. For teachers, learning outcomes included a greater appreciation for diversity, a greater understanding of self and others, and a deeper understanding of the dimensions of power. Seven principles and three corollaries were elicited from the data. These principles identify conditions for positive collaborative relationships between teachers and adult students.